RESEARCH ON LOAD FLUCTUATION CHARACTERISTICS OF SUPPORT BEARING RACEWAY FOR SPECIAL VEHICLE LIFT MECHANISM - WANG ZhongLei; SUN HaiBo (Jixie qiangdu)
The load fluctuation of the transmission system are important factors that cause equipment fatigue,and the fatigue failure has been the most common failure mode of the transmission system. Therefore,a special vehicle lift mechanism transmission system has been regarded as the research object,the three-dimensional model of the main components of the transmission system has been established,and the influences of the bolt design on the load fluctuation characteristics of support bearing raceway of transmission system have been analyzed by the finite element and vibration frequency detection methods. The research results show that the bolt pre-tightening force in the transmission system change the contact deformation of the raceway of the supporting bearing and then affect the contact load of the supporting bearing. Under the combination influence of the bolt pretightening force and the external load,the supporting bearing contact load fluctuate greatly,which reduce the fatigue life of the supports bearing of transmission system obviously. The optimization of the wall thickness of the supports bearing,reducing the pre-tightening force of the bolt,and increasing the distance between the bolt hole and the supports bearing can effectively reduce the cyclic fluctuation load for the supports bearing of transmission system,thereby improving the fatigue life of the transmission system; the vibration of the transmission system was reduced after optimization. The research provides a theoretical basis for the comprehensive transmission improvement of the performance of transmission system,and the improvement of the fatigue life of the support bearing.